Synthesis of Functionalized Diketopiperazines as Cyclotryprostatin and Tryprostatin Analogues - Nguyen Van, Tuyen; Claes, Pieter; De Kimpe, Norbert (Synlett, 2013)
Various ketopiperazines were synthesized as (cyclo)tryprostatin analogues. Construction of the skeleton started with a Pictet–Spengler reaction followed by acylation or alkylation of the piperidine nitrogen and condensation with a primary amine. 2-Chloroacetyl tetrahydro-β-carbolines rearranged towards the corresponding 2-chloro-N-[2-(1H-indol-3-yl)ethyl]acetamide deriv-atives upon treatment with NBS. These compounds were cyclized with primary amines towards the corresponding functionalized diketopiperazines.
Keywords: (di)ketopiperazines; bromoindolenium rearrangement; (cyclo)tryprostatin; tetrahydro-β-carbolines